Concurrent fast growth of sub-centimeter single-crystal graphene with controlled nucleation density in a confined channel. Issue 27 (30th June 2017) - Wu, Ruizhe; Pan, Jie; Ou, Xuewu; Zhang, Qicheng; Ding, Yao; Sheng, Ping; Luo, Zhengtang
Abstract : A simple Cu channel structure over Cu/quartz support was designed to achieve fast growth of sub-centimeter single-crystal graphene grains. Abstract : The synthesis of large-domain-sized graphene requires a low nucleation density, which inevitably leads to a reduced growth rate. To achieve both a large domain size and high growth rate, we designed a simple channel structure that allowed us to control the nucleation density by tuning the flow dynamics and by introducing an additional catalyst inside to control the growth kinetics at the same time. The designed channel structure plays three roles in the growth of graphene: (1) it retains oxygen to passivate the active nucleation sites; (2) it restricts the mass transfer of CH4 to control the supersaturation for nucleation; and (3) it provides additional catalytic sites for the decomposition of CH4 to boost the graphene growth rate. Our strategy allowed the successful preparation of sub-centimeter-domain-sized graphene in 1 h with an average growth rate of 70 μm min −1, and with a hole mobility of 5500 cm 2 V −1 S −1, which is sufficient for practical applications. Our method paves the way for the large-scale production of single-crystal graphene or other 2D materials at a highly efficient level.